Financing models of vocational education and its impact on the economy: Problems and perspectives - George Abuselidze; Lasha Beridze (SHS Web Conferences: ERPA International Congresses on Education 2019 (ERPA 2019), Sakarya, Turkey, June 19-22, 2019, 2019)
Vocational education and related financial support are one of the priorities of the countries policy at the present stage. Education is the fundamental foundation that is necessary for development of the world. While the deterioration of the socio-economic situation in transition in Georgia, inadequate economic policies, the adoption of inappropriate employment decisions, the use of models used by developed countries, and many others, caused the departure of vocational education space in the country. In the survey is studied vocational education financing models of developed countries and the education policy of Georgia. The research process uses the qualitative and quantitative method of data collection. The work is undertaken in depth research of the current model of funding of vocational education programs, analysis and relevant conclusions.
Keywords: 330